Optimized chaos based encryption-decryption of multimedia data - Rashad J. Rasras; Mutaz Rasmi Abu Sara; Jihad Nader; Ziad Alqadi (Bulletin of Electrical Engineering and Informatics, 2026)
These days, a major concern is the security of multimedia data exchange over the internet. Compared to conventional methods, chaos-based encryption has proven increasing role and superiority in current multimedia cryptography. This research proposes an innovative multimedia encryption technique utilizing optimized chaotic systems and simple rearrangement operation. Data blocking will be used to optimize the chaotic model and to reduce the key generation time. To increase the private key length and to raise the level of data security the presented method will be implemented in multiple rounds, where each round will be treated as an independent task and the selected sequence of rounds to be executed depends on the user wish. The method can be efficiently used to cipher-decipher short messages, images, and digital speech signal, and it will use variable length of private key, variable block size and variable number of rounds. The output of simulation confirms effectiveness of proposed technique in giving strong security, and good speed up in ciphering and deciphering process comparing with other existing standard and chaotic based methods. The proposed technique shows high resistance to attacks while the quality of encrypted/decrypted digital data remains acceptable.